2021
DOI: 10.1371/journal.pone.0256081
|View full text |Cite
|
Sign up to set email alerts
|

Three hundred years of Palmyrene history. Unlocking archaeological data for studying past societal transformations

Abstract: While archaeological sciences have made great advances over the last decades through combining archaeological evidence and natural sciences in order to push borders for the understanding of archaeological contexts, traditional archaeology still holds an immense latent potential. Such potential can be realized through baseline projects that pull together unexplored bodies of material culture and study these in detail in order to investigate their significance for the understanding of the human past. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…But another sphere presents good information about individual wealth, and this is the funerary domain, where we can study the commissioning of monuments, tombs, their decoration, and the often lavish funerary sculpture (Raja 2019;. A comprehensive study of all known graves and funerary sculpture has recently shown that these monuments and their developments over time give insight into drops and increases, fluctuations that connect closely to the development of the city overall (Raja, Bobou, and Romanowska 2021;Raja 2022;. Measuring public wealth in Palmyra is difficult.…”
Section: Proxies For Urban Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…But another sphere presents good information about individual wealth, and this is the funerary domain, where we can study the commissioning of monuments, tombs, their decoration, and the often lavish funerary sculpture (Raja 2019;. A comprehensive study of all known graves and funerary sculpture has recently shown that these monuments and their developments over time give insight into drops and increases, fluctuations that connect closely to the development of the city overall (Raja, Bobou, and Romanowska 2021;Raja 2022;. Measuring public wealth in Palmyra is difficult.…”
Section: Proxies For Urban Developmentmentioning
confidence: 99%
“…Hoffman-Salz 2011;2015). Subsistence and demo graphy in ancient Palmyra have received limited attention in past scholarship (but see Crouch 1975;Hauser 2012;Meyer 2017;Raja, Bobou, and Romanowska 2021). With one remarkable, but by all standards outdated exception (Partsch 1922), the relationship between the climate-and urban histories of the site has only been addressed in passing (e.g.…”
mentioning
confidence: 99%
“…2 Yet, many aspects of Palmyra's economy and its environmental implications remain underexplored, whether we consider them in isolation or as part of an interconnected web (Raja and Seland 2022;Romanowska and others 2021). At a certain fundamental level, the materials that the Palmyrenes used routinely for professional or domestic labour and how they got them have not been widely examined until recently (Bobou, Raja, and Romanowska 2021;Raja, Bobou, and Romanowska 2021;Raja and Steding 2021). These new studies also only cover some aspects of the materials used in Palmyra.…”
Section: Palmyra and Its Frameworkmentioning
confidence: 99%
“…Though estimates of Palmyra's population vary, it clearly was a well-populated city with a vast hinterland speckled with nucleated centres (Campmany Jiménez and others forthcoming). Recent studies on the funerary sculpture from the city have shown that we can get closer to understanding flows in the population size over time and can even begin to get closer to the reasons behind such fluctuations, such as disease, military crises, and climate change (Raja, Bobou, and Romanowska 2021;. The people living in Palmyra and its hinterland needed cooked food, storage and transportation vessels, glass, and metal objects.…”
Section: Fuel Energymentioning
confidence: 99%
“…Its location as an individual large urban center in a sparsely populated area and well documented historical trajectory provide clearly demarcated spatio-temporal boundaries. The city was intensively excavated and researched for more than a century providing a diverse range of evidence types that can be used to contextualise findings [12][13][14][15][16][17]. Although there had been little focus on Palmyra's hinterland in early research, more recent work has started to address this gap, providing much needed data about the land surrounding the city [18][19][20].…”
Section: Introductionmentioning
confidence: 99%